Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex - Haran, Julien M.; Hansen, Steffan; Benoit, Laure; Addison, Pia (European Journal of Taxonomy, 2020)
Phlyctinus callosus (Schoenherr, 1826) (Curculionidae, Entiminae, Oosomini) is a species native to the Western Cape province of the Republic of South Africa. It is regarded as a key pest of orchards and vineyards. Detailed observations of its morphology and ecology have shown this species to be a complex of closely related species. In this study we describe the species of this complex, provide morphological and molecular diagnostic tools to distinguish between species, and review their distribution and host plant associations. In all, six species are recognized in the P. callosus complex and five are described as new (P. grootbosensis Haran sp. nov., P. xerophilus Haran sp. nov., P. planithorax Haran sp. nov., P. littoralis Haran sp. nov., P. aloevorus Haran sp. nov.). Sequences of the mitochondrial gene used (cytochrome oxidase I, COI) indicated that P. xerophilus Haran sp. nov. might comprise several cryptic species for which stable morphological features could not be identified at this stage. The species of the genus Phlyctinus appear to be primarily associated with various Asteraceae found in humid, sandy and disturbed habitats.